2009
DOI: 10.1017/s0031182009991077
|View full text |Cite
|
Sign up to set email alerts
|

Biological invasion and parasitism: invaders do not suffer from physiological alterations of the acanthocephalanPomphorhynchus laevis

Abstract: Biological invasions expose parasites to new invasive hosts in addition to their local hosts. However, local parasites are often less successful in infecting and exploiting their new hosts. This may have major consequences for the competitive ability of hosts, and finally on the fate of the parasite-host community. In Burgundy (Eastern France), the acanthocephalan parasite, Pomphorhynchus laevis, infects 2 amphipod species living in sympatry: the native Gammarus pulex and the invasive Gammarus roeseli. While P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…These results are in accordance with those obtained in one of our previous studies [25] and also with those of Plaistow et al [7] or Cornet et al [47] who have observed an increase of glycogen content and a tendency of decrease in lipids content, respectively. Lipid depletion could be explained by the fact that parasites draw out energy for their own development from their host [48].…”
Section: Discussionsupporting
confidence: 94%
“…These results are in accordance with those obtained in one of our previous studies [25] and also with those of Plaistow et al [7] or Cornet et al [47] who have observed an increase of glycogen content and a tendency of decrease in lipids content, respectively. Lipid depletion could be explained by the fact that parasites draw out energy for their own development from their host [48].…”
Section: Discussionsupporting
confidence: 94%
“…Systemic mechanisms such as acute phase protein activity, anorexia, lethargy, and fever are highly inflammatory, and thus may be ‘costly’ (Klasing & Leshchinsky, 1999). These responses are predicted (Cornet et al, 2016; Lee & Klasing, 2004), and have been shown, to be down-regulated in invasive populations of invertebrates (Cornet, Sorci & Moret, 2010; Wilson-Rich & Starks, 2010), sparrows (Lee, Martin & Wikelski, 2005), trout (Monzon-Arguello et al, 2014), and deer (Quéméré et al, 2015). Although constitutive innate defences (such as whole-blood phagocytosis of bacteria or yeast) also require substantial energy to activate (McDade, Georgiev & Kuzawa, 2016), glucose metabolism does not increase during phagocytosis in human neutrophils (Borregaard & Herlin, 1982).…”
Section: Introductionmentioning
confidence: 90%
“…A sustained activation of immune system effector proteins (cytokines) is necessary to maintain resistance to acute and chronic T. gondii infections, and this alone could alter neuromodulator activity (Webster and McConkey, 2010). One additional consideration for this hypothesis is the pattern of parasites that are unable to modify the behavior of non-native hosts, indicating a level of local adaptation to the native host immune system and perhaps a clue to mechanisms of behavior modification (Ballabeni and Ward, 1993;Cornet et al, 2010;Tain et al, 2006).…”
Section: Neuromodulationmentioning
confidence: 99%